PENGARUH PENERAPAN METOD PROJECT BASED LEARNING UNTUK MENINGKATKAN MINAT WIRAUSAHA SISWA PADA PEMBELAJARAN PAI STUDI QUASI EKSPERIMEN DI KELAS X SMK 4 KOTA JAMBI - Meila Mericce; Sukarno; Samsu (STKIP Subang, 2026)
integrating islamic knowledge in the field of entrepreneurship is a good opportunity to develop because it has the opportunity to be developed because the indonesian population is the largest muslim in the world. this research aims to apply entrepreneurship-based project-based learning (PJBL) learning based on islamic knowledge. the method used is quantitative with a one-group pretest–posttest design. a likert scale questionnaire is used to measure students' achievement of entrepreneurial interest before and after learning. the research results showed that students experienced an increase in interest in entrepreneurship after the learning was carried out, where the average achievement of students reached 86.68% in the very high category. this research is only designed to produce product designs based on islamic concepts. future research is expected to be able to develop entrepreneurship-based pjbl learning to produce marketable products. keywords: entrepreneurship learning, project based-learning,